THE DEVELOPMENT OF MOVEMENT AND INFLUENCE OF A THARIQAH ON THE TRANSFORMATION OF THE SOCIO-RELIGIOUS ATTITUDES OF ITS CONGREGATION - Abitolkha, Amir Maliki (European journal for philosophy of religion, 2023)
The thariqah is a transformation of Sufism into religious behavior as a tangible result of the practice of its teachings. This article uses a normative, historical, psycho-sociological approach to examining the development of the thariqah movement and proving its influence on changes in the social and religious attitudes of the community. The results of this study are the development of the thariqah movement occurs on the change of Sufism from individual spiritual behavior to social behavior, even to social movements. This development occurs in three stages; khanaqah, tariqah, and ta’ifah. The influence of the thariqah on changes in religious social attitudes. First, individuals become associated with a particular order. The main reason for an individual's attachment to a ta’ifah is family relationships and reasons for survival, namely the spiritual, social, and economic benefits of the pattern of that relationship. Second, everyone and their family can choose their ta’ifah. Third, the relationship between Sufi and ceremonial brotherhood fulfills not only the function of brotherhood but also the function of the people of each village or part of the city where everyone belongs to the community.